Densities, Viscosities and Viscosity Deviations of Binary Liquid Mixtures of 2-Butanol with Non-Polar Solvent at 303.15 K - SHARMA, DHIRENDRA; TRIVEDI, ANAND (Asian Journal of Chemistry, 2010)
Densities and viscosities have been measured for the binary liquid mixtures of 2-butanol with some non-polar solvent e.g., Benzene, toluene, xylene, hexane and carbon tetrachloride over the entire composition range at 303.15K. From density and viscosity data, the values of viscosity deviation (Dh) of the binary mixtures have been determined at 303.15 K. The excess properties are found to be negative depending on the molecular interactions and the nature of liquid mixtures